Hungarian Monitoring, 19 July 1990 . [Magyar rádiófigyelő], 1990. július 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Romanian sportspeople request asylum in Sweden - Delors's Moscow visit - Growing tension in Kyrgyzstan - Extreme right growing stronger in the FRG Domestic Affairs: - Hungarian-American economic relations - International student group helps to repair Ferenc József barracks - Hungarian director appointed as head of prestigious Viennese museum Economy: - On increasing employment funds Külpolitika: - Román sportolók menedékjogi kérelme Svédországba - Delors moszkvai látogatása - Növekvő feszültség Kirgizisztánban - Erősödő szélsőjobb az NSZK-ban Belpolitika: - Magyar-amerikai gazdasági kapcsolatok - Nemzetközi diákcsoport segít rendbehozni a Ferenc József laktanyát - Magyar igazgató egy rangos bécsi múzeumban Gazdaság: - A foglalkoztatási alap növeléséről